2023
DOI: 10.1021/acs.est.3c05195
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane Foam Emission Samplers to Identify Sources of Airborne Polychlorinated Biphenyls from Glass-Block Windows and Other Room Surfaces in a Vermont School

Jason B. X. Hua,
Rachel F. Marek,
Keri C. Hornbuckle

Abstract: We hypothesized that emissions of polychlorinated biphenyls (PCBs) from Aroclor mixtures present in building materials explain their concentrations in school air. Here, we report a study of airborne concentrations and gas-phase emissions in three elementary school rooms constructed in 1958. We collected airborne PCBs using polyurethane foam passive air samplers (PUF-PAS, n = 6) and PCB emissions from building materials using polyurethane foam passive emission samplers (PUF-PES, n = 17) placed over flat surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In the current study, we have assessed the mitochondrial toxicity of PCB52, a tetra-chlorinated biphenyl that is one of the most abundantly found lower-chlorinated biphenyl (LC-PCB) congeners in air, along with its human-relevant metabolites. , Exposure to LC-PCBs is a public health concern as they continue to be produced even today as byproducts of chemical manufacturing processes such as the paint and pigment production processes. , Serum levels of PCBs in populations exposed to PCBs without high dietary exposure had PCB levels ranging from undetectable to ∼650 ng/g lw . Total PCB levels in human brain samples from older adults ranged from 32 to 3050 pg/g ww, while those in neonatal brain samples ranged from undetectable to ∼2800 pg/g ww .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study, we have assessed the mitochondrial toxicity of PCB52, a tetra-chlorinated biphenyl that is one of the most abundantly found lower-chlorinated biphenyl (LC-PCB) congeners in air, along with its human-relevant metabolites. , Exposure to LC-PCBs is a public health concern as they continue to be produced even today as byproducts of chemical manufacturing processes such as the paint and pigment production processes. , Serum levels of PCBs in populations exposed to PCBs without high dietary exposure had PCB levels ranging from undetectable to ∼650 ng/g lw . Total PCB levels in human brain samples from older adults ranged from 32 to 3050 pg/g ww, while those in neonatal brain samples ranged from undetectable to ∼2800 pg/g ww .…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have explored the effects of PCBs on astrocytes and the role of astrocytes in PCB-induced neurotoxicity. Previously, we have shown that the rat astroglial C6 cell line and primary astrocytes from rats and mice are susceptible to adverse effects via PCB exposure . PCB52 is an ortho-substituted, nondioxin-like, tetra-chlorinated biphenyl compound that is one of the most abundantly found PCB congeners in air samples contaminated with PCBs. , While previous work established the toxicity of PCB52 and its human-relevant metabolites for C6 cells and primary astrocytes, the cellular targets yielding the adverse outcomes were not identified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation